Disparate Approaches to Intimate Partner Violence Intervention: A Preliminary Investigation of Participant Outcomes across Two Community-based Programs. Issue 11 (2nd November 2021) - Bouchard, Jessica; Wong, Jennifer S.
ABSTRACT: There exists ongoing debate regarding appropriate therapeutic approaches, practices, and techniques for interventions targeted toward male perpetrators of intimate partner violence (IPV). The current study describes and presents pilot evaluation data from two IPV intervention programs implemented in British Columbia, Canada which use different approaches to IPV intervention: Help Yourself to Healthy Relationships ( HYHR ; a feminist/trauma-informed program), and Managing Stress and Personal Relationships ( MSPR ; a cognitive-behavior therapy (CBT)-oriented anger/stress management program). This pilot comparative evaluation examines quantitative outcomes focused on self-reported changes in participant psychological and physical abuse toward their intimate partners, and a series of questions assessing feedback about the program content, lessons learned, and overall satisfaction. Findings from the evaluation suggest that MSPR was more effective at reducing rates of psychological violence than was HYHR . In addition, regardless of which program they participated in, participants discussed the importance of learning how to understand, manage, and regulate their emotions. Limitations of the current study and implications for the development and improvement of future IPV intervention programs are discussed.